Penerapan Protokol Kesehatan Masa Pandemi Covid-19 Sekolah Dasar Negeri 003 Pasenggerahan - Wahyu Hidayat; M. Kamali Zaman (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2022)
The Covid-19 pandemic requires us to limit physical interaction and contact to avoid the transmission of Covid-19. This restriction also applies to the learning process in schools, so that learning from becomes an option. Evaluation of ineffective online learning requires face-to-face learning to be carried out by students. On the other hand, the readiness of schools to implement face-to-face school health protocols is also still experiencing obstacles. This study aims to evaluate the Application of Health Protocols During the Covid-19 Pandemic Period at 003 Pasenggerahan State Elementary School. This evaluation research uses a qualitative approach, where researchers evaluate the implementation of education during the COVID-19 pandemic at SDN 003 Pesangrahan. The results of the study illustrate that administrative readiness has been fulfilled, the readiness of supporting facilities and equipment has been complete. In addition, the development of health protocol habits has been carried out, as well as sustainability efforts have also been carried out well. The conclusion from the research, administratively and technically, limited face-to-face school requirements can be done at SDN 003 Pasenggarahan. Suggestions can be given to managers to form a Covid-19 task force, rather that limited face-to-face education can be monitored continuously.